2015
DOI: 10.1016/j.jtcvs.2014.08.020
|View full text |Cite
|
Sign up to set email alerts
|

Stage 1 hybrid palliation for hypoplastic left heart syndrome—assessment of contemporary patterns of use: An analysis of The Society of Thoracic Surgeons Congenital Heart Surgery Database

Abstract: Objective Hybrid palliation is an alternative to Norwood stage 1 for the initial management of hypoplastic left heart syndrome. Contemporary multicenter hybrid use and institutional/patient factors associated with hybrid use relative to the Norwood have not been evaluated. We describe hybrid use in relation to institutional volume, patient factors, and short-term outcomes. Methods Infants aged 60 days or less listed in The Society of Thoracic Surgeons Congenital Heart Surgery Database (2010–2012) undergoing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
69
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(74 citation statements)
references
References 21 publications
0
69
0
5
Order By: Relevance
“…The procedure has been used by many centers but deployed preferentially over the Norwood procedure by only a few. 50 Most centers select the hybrid approach for high-risk Norwood candidates (those with prematurity, low birth weight, hemodynamic instability, or brain or other noncardiac conditions that could affect the safety of aortic reconstruction at birth) and for those who may be able to undergo a 2-ventricle repair later. 51 Some of these patients do eventually go on to receive a transplant.…”
Section: February 23 2016mentioning
confidence: 99%
See 1 more Smart Citation
“…The procedure has been used by many centers but deployed preferentially over the Norwood procedure by only a few. 50 Most centers select the hybrid approach for high-risk Norwood candidates (those with prematurity, low birth weight, hemodynamic instability, or brain or other noncardiac conditions that could affect the safety of aortic reconstruction at birth) and for those who may be able to undergo a 2-ventricle repair later. 51 Some of these patients do eventually go on to receive a transplant.…”
Section: February 23 2016mentioning
confidence: 99%
“…51 Some of these patients do eventually go on to receive a transplant. 50,52 Despite the fact that some high-risk Norwood candidates may be offered primary transplantation, no study to date has specifically described the use of the hybrid approach as a bridge to transplantation.…”
Section: February 23 2016mentioning
confidence: 99%
“…For this reason, we did not include completeness of revascularization in our analysis. Whereas their series 1 suggested that completeness of revascularization increases the benefit from TAR, the reverse has been reported by Kieser and colleagues, 3 who suggested that in their Canadian experience the use of arterial grafts in fact negated (or mitigated) the impact of incomplete revascularization. 3 (3) The application of TAR in our series has been broader than that reported in their 1 and other published series, which likely reflects some international differences in practice, although we believe that the results can be generalized.…”
mentioning
confidence: 93%
“…Whereas their series 1 suggested that completeness of revascularization increases the benefit from TAR, the reverse has been reported by Kieser and colleagues, 3 who suggested that in their Canadian experience the use of arterial grafts in fact negated (or mitigated) the impact of incomplete revascularization. 3 (3) The application of TAR in our series has been broader than that reported in their 1 and other published series, which likely reflects some international differences in practice, although we believe that the results can be generalized. We are not certain, however, whether the use of TAR could be even higher, as our colleagues have suggested, because of the rise in radial angiography and uncertainty regarding the safety of using as bypass conduits radial arteries that have been cannulated for angiography.…”
mentioning
confidence: 93%
See 1 more Smart Citation